Chemical composition changes of Auxis rochei between summer and winter (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2025)
This research aims to study the effect of seasonal variation on the chemical composition of one of Scombridae family the species (Auxis rochei). The samples were collected from Syrian Marine Waters (Alssaid and Alnozha Marina known in AlYugoslavia as a boats departure station) during the summer and winter seasons of 2022 and 2023. The study analyzed the impact of seasonal changes on the chemical composition of edible part (Head, tail, gills, viscera and spine removed) by determining the percentages of protein, fat, moisture, and ash.The results of the chemical analysis during summer were as follows: moisture (74.24%), protein (21.10%), fat (1.65%), and ash (1.813%). During winter, the values were moisture (73.96%), protein (20.71%), fat (1.73%), and ash (2.07%). The results showed that the average protein was higher in summer compared to winter, while the average fat was relatively higher in winter compared to summer, due to fish consuming the fat decomposition energy for formation the reproductive units. More ever the protein and fat values changes with the seasons. The moisture and ash percentages were similar in both seasons.
Keywords: Chemical composition, protein, fat, (Auxis rochei), Syrian Marine Waters